MENINGKATAN AKTIVITAS BELAJAR DAN HASIL BELAJAR SISWA MELALUI METODE PROBLEM BASED LEARNING(PBL) MODEL KOOPERATIF DI KELAS XII IPA-6 SMA NEGERI 1 LUBUK SIKAPING - za, Eli (Menara Ilmu, 2018)
The aim of this research is to improve learning activities and student learning outcomes through themethod of Problem Based Learning (PBL) cooperative model in the application of the concept ofredox and electrochemical reactions in class XII IPA 6 SMAN 1 LubukSikaping the academic year2016/2017. This research was conducted by two cycles in class XII IPA-6 with the number ofstudents 34 people. The learning process was observed in the form of activities and student learningoutcomes by using observation sheet and test results. Student activity was observed using theobservation sheet with five indicators. The observation of learning outcomes utilized four itemsdescription in one cycle and multiple choices as much as 25 points in the two cycle. Based on theobservation of data observer towards the students’ activities in the learning process,student activityon one siklus was obtained 52.3% dramatically increasing to 75.5 % in two cycle. The resultoflearning was obtained by classical completeness value of 61.3% in first cycle to 90% in secondcycle.The observation of student activity has exceeded the criteria above 75% and the study hasshown 90% of students who were completed with classical. The aforementioned evidences revealthat the PBL method can increase the activity of students in the learning of redox reaction and canimprove student learning outcomes classical completeness.Keyword: Problem Based Learning (PBL), activity and learning outcomes